An Analysis of Students’ Error in Writing Recount Text (A Case Study in The Second Grade Students of MA Sunan Ampel Kamal Kuning-Krejengan) - Ummi Azizah; Endah Tri Wisudaningsih; Beny Hamdani (Jurnal Kewarganegaraan, 2022)
Abstract An analysis on the students’ error in writing recount text. The purpose of this research is to identify and classify the types of errors, and the factors that cause errors. There are two objectives of this study; 1. To find out the types of errors made by students in writing recount texts. 2. To detect the causes of errors made by students. The method used in this research is descriptive qualitative with case study research design. Researchers used data collection procedures through observation, interviews, and documentation. The subjects in this research were the second grade students at MA Sunan Ampel Kamalkuning-Krejengan, which consisted of 32 students in one class. The results of this research indicate that the most frequent errors when making recount texts are grammatical errors, especially in the use of tenses, in recount texts using the simple past tense and they make a lot of errors and are fooled when using verb-2 such as the word “go” which should change to “went”, “visit” to “visited”, “stay” to “stayed”, “meet” to “met” because of the past tense. Some students also made errors in the structure of the recount text series, namely orientation, events, and re-orientation in that section, and students also make errors in writing or producing vocabulary, for example “Friend” becomes “frend”, “Last” becomes “lass”, “Week” becomes “wiik/weak/wit”, “Then” becomes “dhen”. In addition, there are several factors that cause errors made by students, namely carelessness or carelessness, first language disorders, and translation. Keywords: Errors Analysis, Recount Text Writing